Metaplastic Carcinoma of the Breast with Squamous Differentiation: A Case Report from the University Teaching Hospital of Kigali (CHUK), Rwanda - Delphine Uwamariya; Carine Nyampinga; Anne Yvette Nsenguwera; Belson Rugwizangoga (Case Reports in Pathology)
Metaplastic breast carcinoma is a rare and aggressive condition, accounting less than 1% of breast malignancies. It presents with large mass and frequently with distant metastasis at time of diagnosis. Morphologically, it is characterized by the differentiation of neoplastic epithelium into epithelial or mesenchymal-looking elements like squamous cells, spindle cells, cartilage, or bone and has poor prognosis with its triple negative status.